toner

The toner formulation with a binder resin and fatty acid metal salt stabilizes wax within particles, addressing wax seepage issues and maintaining fluidity, thus ensuring excellent fixing properties and image quality over time.

JP7612374B2Active Publication Date: 2025-01-14CANON KK
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2020178378
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-23
Publication Date
2025-01-14
Estimated Expiration
2040-10-23

AI Technical Summary

Technical Problem

Existing toners suffer from insufficient offset resistance and reduced fluidity due to wax seepage during long-term use, leading to decreased performance in fixing properties and image quality.

Method used

A toner formulation containing a binder resin, resin A with a substituted or unsubstituted silyl group, and a fatty acid metal salt, where the resin A interacts with the fatty acid metal salt to stabilize the wax within the toner particles, preventing wax seepage and maintaining fluidity.

Benefits of technology

The toner exhibits excellent fixing properties and fluidity even during long-term use, enhancing image quality and performance stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612374000012
    Figure 0007612374000012
  • Figure 0007612374000001
    Figure 0007612374000001
  • Figure 0007612374000002
    Figure 0007612374000002
Patent Text Reader

Abstract

To provide a toner that has excellent fixability and has excellent flowability even during long-term use.SOLUTION: A toner contains a toner particle, where the toner particle comprises a binder resin, a resin A, a wax, and a fatty acid metal salt, the resin A has a substituted or unsubstituted silyl group in a molecule, and a substituent of the substituted silyl group is at least one selected from the group consisting of an alkyl group having one or more carbon atoms, an alkoxy group having one or more carbon atoms, a hydroxy group, a halogen atom, and an aryl group having 6 or more carbon atoms.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a toner used in a recording method utilizing electrophotography or the like. [Background technology]

[0002] In recent years, image forming apparatuses such as copiers and printers are being required to operate at higher speeds and with longer lifespans as their intended purposes and environments become more diverse. In particular, toners with excellent fixability and fluidity are being required to meet the increasing demands for higher process speeds and longer lifespans. Patent Document 1 discloses that by using a hybrid resin containing a condensation polymerization resin unit and an addition polymerization resin unit as a wax dispersant and an ester wax as a release agent, the wax in the toner can be dispersed effectively, thereby improving the low-temperature fixing property and heat-resistant storage stability of the toner. In Patent Document 2, offset resistance is improved by containing, as a binder resin, a vinyl resin obtained by copolymerizing a vinyl monomer with a silane coupling agent having an unsaturated double bond and an alkoxysilyl group. In Patent Document 3, an external additive and a specific fatty acid metal salt are externally added to a toner base material to improve the fluidity of the toner. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-151513 A [Patent Document 2] Japanese Patent Application Publication No. 7-239573 [Patent Document 3] JP 2007-79304 A Summary of the Invention [Problem to be solved by the invention]

[0004] However, it was found that the toner described in Patent Document 1 has insufficient offset resistance because the compatibility between the wax and the binder resin is increased by the wax dispersant, which suppresses the exudation of the wax during fixing. Moreover, it was found that with the toner described in Patent Document 2, the wax seeps out onto the toner surface during long-term use, reducing fluidity and causing problems with solid print conformability. Furthermore, it was found that the toner described in Patent Document 3 has a tendency that the externally added fatty acid metal salt is detached from the toner matrix during long-term use, and there is still room for improvement in terms of maintaining fluidity.

[0005] The present disclosure provides a toner that has excellent fixability and excellent fluidity even during long-term use. [Means for solving the problem]

[0006] The present disclosure provides a toner comprising toner particles, the toner particles contain a binder resin, a resin A, a wax and a fatty acid metal salt; The resin A has a substituted or unsubstituted silyl group in the molecule, And has a structure represented by the following formula (1): [ka] (In the formula (1), P 1 represents the polymer moiety, and L 1 represents a single bond or a divalent linking group, R 1 ~R 3 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 or more carbon atoms, an alkoxy group having 1 or more carbon atoms, an aryl group having 6 or more carbon atoms, or a hydroxyl group; m represents a positive integer; and when m is 2 or more, 1 , multiple R 1 , multiple R 2 and multiple R 3 may be the same or different.) The substituent of the substituted silyl group is at least one selected from the group consisting of an alkyl group having 1 or more carbon atoms, an alkoxy group having 1 or more carbon atoms, a hydroxy group, a halogen atom, and an aryl group having 6 or more carbon atoms. The toner is characterized in that: Effect of the Invention

[0007] According to the present disclosure, there is provided a toner having excellent fixability and excellent fluidity even during long-term use. It is possible. [Brief description of the drawings]

[0008] [Figure 1] This is a device for measuring the amount of charge. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The embodiments are described in detail below, but the present disclosure is not limited to the following description. In the present disclosure, the expressions "XX or more and YY or less" and "XX to YY" representing a numerical range mean a numerical range including the endpoints, that is, the lower limit and the upper limit, unless otherwise specified.

[0010] The present disclosure provides a toner comprising toner particles, the toner particles contain a binder resin, a resin A, a wax and a fatty acid metal salt; The resin A has a substituted or unsubstituted silyl group in the molecule, The substituent of the substituted silyl group is at least one selected from the group consisting of an alkyl group having 1 or more carbon atoms, an alkoxy group having 1 or more carbon atoms, a hydroxy group, a halogen atom, and an aryl group having 6 or more carbon atoms. The toner is characterized in that:

[0011] The present inventors have found that by employing a toner having the above-described configuration, it is possible to provide a toner that has excellent fixing properties and excellent fluidity even during long-term use. The present inventors speculate that the reason for this is as follows. Conventional toners with excellent low-temperature fixing properties change in composition on the toner surface due to stresses such as heat and impacts in the developing machine when used for a long period of time, causing wax components to seep out onto the toner surface and reducing fluidity. On the other hand, when wax dispersants are used to suppress wax seepage, wax seepage during fixing is also suppressed, resulting in issues with offset resistance. The toner of the present disclosure contains toner particles containing a binder resin, a resin A, a fatty acid metal salt, and a wax, and the resin A has a substituted or unsubstituted silyl group in the molecule. It is considered that the resin A and the fatty acid metal salt form a complex by the interaction between the silicon atom of the silyl group in the resin A and the oxygen atom site adjacent to the metal of the fatty acid metal salt, and the interaction between the oxygen atom site in the substituent of the silyl group in the resin A and the metal site of the fatty acid metal salt. In addition, the fatty acid metal salt and the wax have a high affinity because of their similar structures, and it is considered that the complex of the resin A and the fatty acid metal salt uniformly disperses the wax in the toner particles and stabilizes the wax. Therefore, it is considered that the exudation of the wax to the toner surface is suppressed during long-term use, and the decrease in fluidity is suppressed. On the other hand, since the interaction between resin A and fatty acid metal salt is not a covalent bond, the molecular mobility increases due to heat during fixing, and the interaction is broken. Therefore, the wax stabilized by the complex of resin A and fatty acid metal salt becomes able to seep out to the toner surface, which is believed to exert a releasing effect and result in offset resistance.

[0012] The constituent elements of the present disclosure will be described in detail below. <Resin A> The toner particles contain a resin A. Resin A (i) has a substituted or unsubstituted silyl group in the molecule, and (ii) the substituent of the substituted silyl group is at least one selected from the group consisting of an alkyl group having one or more carbon atoms, an alkoxy group having one or more carbon atoms, a hydroxy group, a halogen atom, and an aryl group having six or more carbon atoms. The alkyl group preferably has 1-20 carbon atoms, and more preferably 1-4 carbon atoms. The alkoxy group preferably has 1 to 20 carbon atoms, more preferably 1 to 4 carbon atoms, further preferably 1 to 3 carbon atoms, and particularly preferably 1 or 2 carbon atoms. The aryl group preferably has 6 to 14 carbon atoms, and more preferably 6 to 10 carbon atoms. Examples of resin A are not limited as long as they satisfy the above (i) and (ii), but include resins chemically bonded with silane coupling agents, polymers of organosilicon compounds, and hybrid resins thereof. More specifically, resins obtained by modifying polyester resins, vinyl resins, polycarbonate resins, polyurethane resins, phenol resins, epoxy resins, polyolefin resins, or styrene-acrylic resins with silane coupling agents and / or silicone oils, etc., are included.

[0013] Resin A preferably has a structure represented by the following formula (1).

[0014] [ka]

[0015] In the formula (1), P 1 represents the polymer moiety, and L 1 represents a single bond or a divalent linking group, R 1 ~R 3 each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 or more carbon atoms, an alkoxy group having 1 or more carbon atoms, an aryl group having 6 or more carbon atoms, or a hydroxyl group; m represents a positive integer; and when m is 2 or more, 1 , multiple R 1 , multiple R 2 and multiple R 3 may be the same or different. When Resin A has the structure represented by the above formula (1), the interaction with the fatty acid metal salt becomes stronger, and the effect of suppressing the bleeding of wax during long-term use becomes higher.

[0016] R in the above formula (1) 1~R 3 At least one of the R in formula (1) is preferably an alkoxy group having one or more carbon atoms or a hydroxy group. 1 ~R 3 Each of the independently represents an alkoxy group having one or more carbon atoms or a hydroxy group. The presence of an alkoxy group having one or more carbon atoms or a hydroxy group further strengthens the interaction between the fatty acid metal salt and the metal salt, which is thought to further suppress the bleeding of wax during long-term use. Of the above substituents, the number of carbon atoms in the alkyl group is preferably 1 to 20, more preferably 1 to 4. The number of carbon atoms in the alkoxy group is preferably 1 to 20, more preferably 1 to 4, even more preferably 1 to 3, and particularly preferably 1 or 2. The number of carbon atoms in the aryl group is preferably 6 to 14, more preferably 6 to 10. Within this range, the interaction with the fatty acid metal salt is better.

[0017] The content of silicon atoms in resin A is preferably 0.02% by mass to 10.00% by mass. By making it 0.02% by mass or more, the interaction with the fatty acid metal salt occurs more favorably. Also, by making it 10.00% by mass or less, resin A becomes more compatible with the binder resin, so that the complex of resin A and fatty acid metal salt can disperse the wax more uniformly in the toner particles. The content of silicon atoms in resin A is more preferably 0.10% by mass to 5.00% by mass, and further preferably 0.15% by mass to 2.00% by mass. The silicon atom content in Resin A can be controlled by adjusting the amount of silicon compound used in producing Resin A.

[0018] The content of resin A in the toner particles is preferably 0.05% by mass to 90.00% by mass, and more preferably 0.05% by mass to 10.00% by mass. When the content of resin A in the toner is 0.05% by mass or more, the wax is more preferably dispersed in the toner, and when it is 90.00% by mass or less, the low-temperature fixability is further improved.

[0019] R in the above formula (1) 1 ~R 3 In order to make one or more of R into a hydroxy group, 1 ~R 3 Resin A in which one or more of the above groups are alkoxy groups may be hydrolyzed to convert the alkoxy groups into hydroxy groups. The hydrolysis may be carried out by any method, for example, the following method. R in the above formula (1) 1 ~R 3 Resin A, in which one or more of the above groups are alkoxy groups, is dissolved or suspended in a suitable solvent (which may be a polymerizable monomer), and the pH is adjusted to acidic using an acid or alkali, followed by mixing and hydrolysis. Furthermore, hydrolysis may occur during the production of toner particles.

[0020] P in the above formula (1) 1 Examples of the resin moiety include, but are not limited to, a polyester resin moiety, a vinyl resin moiety, a styrene acrylic resin moiety, a polyurethane resin moiety, a polycarbonate resin moiety, a phenolic resin moiety, and a polyolefin resin moiety. Among these, P 1 It is preferable that the resin moiety contains a polyester resin moiety or a styrene-acrylic resin moiety. For example, the resin moiety may be a hybrid resin moiety of a polyester resin and a styrene-acrylic resin.

[0021] The weight average molecular weight (Mw) of resin A is preferably 3000 to 100000, and more preferably 3000 to 30000. By making resin A have an Mw of 3000 or more, the exudation of wax can be further suppressed, and by making it 100000 or less, the compatibility with the binder resin can be further increased, and the wax can be more satisfactorily dispersed. The Mw of the resin A can be controlled by various methods depending on the type of resin contained. For example, when a polyester resin portion is contained, it can be controlled by adjusting the charging ratio of the dialcohol and dicarboxylic acid, which are the monomers, or by adjusting the polymerization time. When a styrene-acrylic resin portion is contained, it can be controlled by adjusting the ratio of the vinyl monomer and the polymerization initiator, which are the monomers, or by adjusting the reaction temperature.

[0022] The polyester resin moiety is preferably, but not limited to, a condensate of a dialcohol and a dicarboxylic acid. For example, a polyester resin moiety having a structure represented by the following formula (6) and at least one structure (multiple structures can be selected) selected from the group consisting of structures represented by the following formulas (7) to (9) is preferred. Alternatively, a polyester resin moiety having a structure represented by the following formula (10) is also preferred.

[0023] [ka]

[0024] In formula (6), R 9 represents an alkylene group, an alkenylene group, or an arylene group. 10 represents an alkylene group or a phenylene group. 18 represents an ethylene group or a propylene group. x and y are each an integer of 0 or more, and the average value of x+y is 2 to 10. In formula (10), R 11 represents an alkylene group or an alkenylene group.

[0025] R in the above formula (6) 9 Examples of the alkylene group (preferably having 1 to 12 carbon atoms) in the above formula include the following: a methylene group, an ethylene group, a trimethylene group, a propylene group, a tetramethylene group, a hexamethylene group, a neopentylene group, a heptamethylene group, an octamethylene group, a nonamethylene group, a decamethylene group, an undecamethylene group, a dodecamethylene group, 1,3-cyclopentylene, 1,3-cyclohexylene, and 1,4-cyclohexylene group. R in the above formula (6) 9 Examples of the alkenylene group (preferably having 2 to 4 carbon atoms) in the formula include a vinylene group, a propenylene group, and a 2-butenylene group. R in the above formula (6) 9 Examples of the arylene group (preferably having 6 to 12 carbon atoms) in the formula include a 1,4-phenylene group, a 1,3-phenylene group, a 1,2-phenylene group, a 2,6-naphthylene group, a 2,7-naphthylene group, and a 4,4'-biphenylene group. R in the above formula (6) 9 may be substituted with a substituent, in which case, examples of the substituent include a methyl group, a halogen atom, a carboxy group, a trifluoromethyl group, and combinations thereof.

[0026] R in the above formula (7) 10 In the above, examples of the alkylene group (preferably having 1 to 12 carbon atoms) include the following: a methylene group, an ethylene group, a trimethylene group, a propylene group, Examples of the aryl group include cyclopentylene, tetramethylene, hexamethylene, neopentylene, heptamethylene, octamethylene, nonamethylene, decamethylene, undecamethylene, dodecamethylene, 1,3-cyclopentylene, 1,3-cyclohexylene, and 1,4-cyclohexylene. R in the above formula (7) 10 Examples of the phenylene group in include a 1,4-phenylene group, a 1,3-phenylene group, and a 1,2-phenylene group. R in the above formula (7) 10 may be substituted with a substituent, in which case, examples of the substituent include a methyl group, an alkoxy group, a hydroxy group, a halogen atom, and combinations thereof.

[0027] R in the above formula (10) 11Examples of the alkylene group (preferably having 2 to 12 carbon atoms) in the above formula include the following: a methylene group, an ethylene group, a trimethylene group, a propylene group, a tetramethylene group, a hexamethylene group, a neopentylene group, a heptamethylene group, an octamethylene group, a nonamethylene group, a decamethylene group, an undecamethylene group, a dodecamethylene group, and a 1,4-cyclohexylene group. R in the above formula (10) 11 In the above, examples of the alkenylene group (preferably having 1 to 40 carbon atoms) include the following: vinylene group, propenylene group, butenylene group, butadienylene group, pentenylene group, hexenylene group, hexadienylene group, heptenylene group, octanylene group, decenylene group, octadecenylene group, eicosenylene group, and triacontenylene group. These alkenylene groups may have any of a linear, branched, and cyclic structure. The position of the double bond may be any position, as long as there is at least one double bond. R in the above formula (10) 11 may be substituted with a substituent. In this case, the substituent that may be substituted includes an alkyl group, an alkoxy group, a hydroxy group, a halogen atom, and combinations thereof.

[0028] The styrene-acrylic resin portion is not particularly limited, and may consist of only styrene-acrylic resin, or may be a block copolymer or graft copolymer of styrene-acrylic resin and another polymer, or a mixture thereof. Here, the styrene-acrylic resin means a copolymer of at least one monomer selected from the group consisting of acrylic acid-based monomers and methacrylic acid-based monomers, and a styrene-based monomer. Examples of the styrene monomer include styrene, α-methylstyrene, β-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, divinylbenzene, etc. The styrene monomer may be used alone or in combination of two or more selected from these. Examples of the acrylic acid monomer include acrylic acid alkyl esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-amyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, and n-nonyl acrylate; acrylic acid diesters such as diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol diacrylate, and 1,6-hexanediol diacrylate; and acrylic acid. Examples of the methacrylic acid monomer include methacrylic acid alkyl esters such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, iso-propyl methacrylate, n-butyl methacrylate, iso-butyl methacrylate, tert-butyl methacrylate, n-amyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, n-octyl methacrylate, and n-nonyl methacrylate; methacrylic acid, and the like. The acrylic acid monomer and the methacrylic acid monomer may be used alone or in combination of two or more selected therefrom.

[0029] The styrene-acrylic resin moiety preferably includes at least one selected from the group consisting of a styrene-acrylic acid alkyl ester copolymer and a styrene-methacrylic acid alkyl ester copolymer. In the total monomers forming the styrene-acrylic resin, the proportion of the styrene-based monomer is preferably 45% by mass or more and 80% by mass or less, while the proportion of at least one monomer selected from the group consisting of an acrylic acid-based monomer and a methacrylic acid-based monomer (for example, at least one selected from the group consisting of an acrylic acid alkyl ester and a methacrylic acid alkyl ester) is preferably 20% by mass or more and 50% by mass or less.

[0030] L in the above formula (1)1 Examples of the divalent linking group that can be represented include structures represented by the following formulas (2) to (5), but are not particularly limited thereto.

[0031] [ka]

[0032] R in Equation (2) 5 represents a single bond, an alkylene group, or an arylene group. (*) represents P in formula (1). 1 R in formula (3) represents a bonding site to the silicon atom in formula (1), and (**) represents a bonding site to the silicon atom in formula (1). 6 represents a single bond, an alkylene group, or an arylene group. (*) represents P in formula (1). 1 R in formulas (4) and (5) represents a bonding site to the silicon atom in formula (1). 7 and R 8 Each of the groups independently represents an alkylene group, an arylene group, or an oxyalkylene group. (*) represents P in the formula (1). 1 represents the bonding site to the silicon atom in formula (1), and (**) represents the bonding site to the silicon atom in formula (1).

[0033] The structure represented by the formula (2) is a divalent linking group containing an amide bond. The linking group can be formed, for example, by reaction of a carboxy group in the resin with an aminosilane. The aminosilane is not particularly limited, but examples thereof include γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, N-phenylγ-aminopropyltriethoxysilane, N-phenylγ-aminopropyltrimethoxysilane, N-β(aminoethyl)γ-aminopropylmethyldimethoxysilane, propyltriethoxysilane, N-6-(aminohexyl)3-aminopropyltrimethoxysilane, 3-aminopropyltrimethylsilane, 3-aminopropylsilane, and the like. R 5 The alkylene group (preferably having 1 to 12 carbon atoms) in is not particularly limited, and may be, for example, an alkylene group containing an --NH-- group. R 5 The arylene group (preferably having 6 to 12 carbon atoms) in the formula (I) is not particularly limited, and may be, for example, an arylene group containing a hetero atom.

[0034] The structure represented by the formula (3) is a divalent linking group containing a urethane bond. The linking group can be formed, for example, by reaction of a hydroxy group in the resin with an isocyanate silane. The isocyanate silane is not particularly limited, but examples thereof include 3-isocyanate propyl trimethoxy silane, 3-isocyanate propyl methyl dimethoxy silane, 3-isocyanate propyl dimethyl methoxy silane, 3-isocyanate propyl triethoxy silane, 3-isocyanate propyl methyl diethoxy silane, and 3-isocyanate propyl dimethyl ethoxy silane. R 6 The alkylene group (preferably having 1 to 12 carbon atoms) in is not particularly limited, and may be, for example, an alkylene group containing an --NH-- group. R 6 The arylene group (preferably having 6 to 12 carbon atoms) in the formula (I) is not particularly limited, and may be, for example, an arylene group containing a hetero atom.

[0035] The structure represented by the formula (4) or (5) is a divalent linking group containing a bond grafted to an ester bond in the resin. The linking group is formed, for example, by an insertion reaction of an epoxysilane. The insertion reaction of epoxysilane refers to a reaction that includes a process of inserting an epoxy group of epoxysilane into an ester bond contained in the main chain of a resin. The insertion reaction referred to here refers to, for example, a reaction described as "insertion reaction of an epoxy compound into an ester bond in a polymer chain" in Organic Synthesis Chemistry, Vol. 49, No. 3, p. 218, 1991. The reaction mechanism of the epoxysilane insertion reaction can be represented by the following model diagram.

[0036] [ka]

[0037] In the figure, D and E indicate the resin constituent parts, and F indicates the epoxy compound constituent part. In the diagram, the ring-opening of the epoxy group can involve α-cleavage or β-cleavage, resulting in two types of compounds. In either case, the epoxy group is inserted into the ester bond in the resin; in other words, the components of the epoxy compound other than the epoxy moiety are grafted to the resin. The epoxy silane is not particularly limited, but examples thereof include β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-glycidoxypropylmethyldiethoxysilane.

[0038] R 7 and R 8 The alkylene group (preferably having 1 to 12 carbon atoms) in is not particularly limited, and may be, for example, an alkylene group containing an --NH-- group. R 7 and R 8 The arylene group (preferably having 6 to 12 carbon atoms) in the formula (I) is not particularly limited, and may be, for example, an arylene group containing a hetero atom. R 7 and R 8The oxyalkylene group (preferably having 1 to 12 carbon atoms) in is not particularly limited, and may be, for example, an oxyalkylene group containing an --NH-- group.

[0039] <Binding resin> The toner particles contain a binder resin. The content of the binder resin in the toner particles is preferably 60% by mass to 90% by mass. As the binder resin, for example, the following resins can be used. Homopolymers of styrene and its substituted derivatives, such as polystyrene and polyvinyltoluene; styrene-based copolymers such as styrene-propylene copolymers, styrene-vinyltoluene copolymers, styrene-vinylnaphthalene copolymers, styrene-methyl acrylate copolymers, styrene-ethyl acrylate copolymers, styrene-butyl acrylate copolymers, styrene-octyl acrylate copolymers, styrene-dimethylaminoethyl acrylate copolymers, styrene-methyl methacrylate copolymers, styrene-ethyl methacrylate copolymers, styrene-butyl methacrylate copolymers, styrene-dimethylaminoethyl methacrylate copolymers, styrene-vinyl methyl ether copolymers, styrene-vinyl ethyl ether copolymers, styrene-vinyl methyl ketone copolymers, styrene-butadiene copolymers, styrene-isoprene copolymers, styrene-maleic acid copolymers, and styrene-maleic acid ester copolymers; Polymethyl methacrylate, polybutyl methacrylate, polyvinyl acetate, polyethylene, polypropylene, polyvinyl butyral, silicone resin, polyester resin, polyamide resin, epoxy resin, polyacrylic resin, rosin, modified rosin, terpene resin, phenol resin, aliphatic or alicyclic hydrocarbon resin, aromatic petroleum resin. These can be used alone or in combination.

[0040] Among them, the content of the styrene-acrylic resin in the binder resin is 50% by mass or more, and P in the formula (1) is 1It is preferable that the content of the polyester resin in the binder resin is 50% by mass or more, and P in the formula (1) 1 It is preferable that P in formula (1) represents a polyester resin moiety. 1 When the portions represented by are the same, the difference in the charge amount of the toner caused by the difference in the environment can be reduced. The present inventors consider this mechanism as follows. When resin A is unevenly distributed and localized in the binder resin, the charge amount of the toner under low temperature and low humidity tends to be significantly larger than the charge amount of the toner under high temperature and high humidity. 1 It is believed that when the portions represented by are the same, the affinity between the binder resin and resin A increases, and resin A disperses more uniformly in the toner, thereby reducing the difference in charge amount caused by differences in the environment.

[0041] <Crosslinking agent> In order to control the molecular weight of the binder resin, a crosslinking agent may be added during polymerization of the polymerizable monomer. As the crosslinking agent, for example, the following compounds can be used, but the crosslinking agent is not limited thereto. Ethylene glycol dimethacrylate, ethylene glycol diacrylate, diethylene glycol dimethacrylate, diethylene glycol diacrylate, triethylene glycol Ricol dimethacrylate, triethylene glycol diacrylate, neopentyl glycol dimethacrylate, neopentyl glycol diacrylate, divinylbenzene, bis(4-acryloxypolyethoxyphenyl)propane, ethylene glycol diacrylate, 1,3-butylene glycol diacrylate, 1,4-butanediol diacrylate, 1,5-pentanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, tetraethylene glycol diacrylate, polyethylene glycol #200, #400, #600 diacrylates, dipropylene glycol diacrylate, polypropylene glycol diacrylate and polyester type diacrylate (MANDA Nippon Kayaku), as well as those in which the above acrylates have been replaced with methacrylates. The amount of the crosslinking agent added is preferably 0.001 to 15.0 parts by mass with respect to 100 parts by mass of the polymerizable monomer.

[0042] <Wax> The toner particles contain a wax. As the wax, for example, the following waxes can be used alone or in combination of two or more kinds, but are not limited thereto. Esters of monohydric alcohols and aliphatic monocarboxylic acids, such as behenyl behenate, stearyl stearate, and palmityl palmitate, or esters of monohydric carboxylic acids and aliphatic monoalcohols; Esters of dihydric alcohols and aliphatic monocarboxylic acids, such as dibehenyl sebacate, hexanediol dibehenate, ethylene glycol distearate, octanediol distearate, ethylene glycol dimontalate, and ethylene glycol dimyristylate, or esters of dihydric carboxylic acids and aliphatic monoalcohols; Esters of trihydric alcohols and aliphatic monocarboxylic acids, such as glycerol tribehenate, or esters of trihydric carboxylic acids and aliphatic monoalcohols; Esters of tetrahydric alcohols and aliphatic monocarboxylic acids, or esters of tetrahydric carboxylic acids and aliphatic monoalcohols, such as pentaerythritol tetrastearate and pentaerythritol tetrapalmitate; Esters of hexavalent alcohols and aliphatic monocarboxylic acids, such as dipentaerythritol hexastearate and dipentaerythritol hexapalmitate, or esters of hexavalent carboxylic acids and aliphatic monoalcohols; Esters of polyhydric alcohols, such as polyglycerol behenate, and aliphatic monocarboxylic acids, or esters of polyhydric carboxylic acids and aliphatic monoalcohols; Natural ester waxes such as carnauba wax and rice wax; Petroleum-based waxes and their derivatives, such as paraffin wax, microcrystalline wax, and petrolatum; Fischer-Tropsch hydrocarbon waxes (Fischer-Tropsch waxes) and their derivatives; Polyolefin waxes such as polyethylene wax and polypropylene wax and their derivatives; Higher aliphatic alcohols; fatty acids such as stearic acid, palmitic acid; Acid amide wax. The wax preferably contains at least one selected from the group consisting of ester wax and aliphatic hydrocarbon wax, which enhances the affinity of the wax with the fatty acid moiety of the fatty acid metal salt described below, thereby improving the dispersion of the wax in the toner. More preferably, the wax in the toner particles contains an ester wax, and the ester wax contains at least one ester compound selected from the group consisting of an ester compound of a fatty acid monomer having 8 to 22 carbon atoms and an alcohol monomer, and an ester compound of an aliphatic alcohol monomer having 8 to 22 carbon atoms and an acid monomer. The melting point of the wax is preferably from 60.0° C. to 100.0° C., and more preferably from 65.0° C. to 90.0° C. When the wax has a melting point of 60.0° C. or higher, the fluidity is less likely to decrease during long-term use, and when the wax has a melting point of 100.0° C. or lower, better low-temperature fixability can be obtained. The wax content in the toner particles is preferably 0.5% by mass to 20.0% by mass.

[0043] <Fatty acid metal salts> The toner particles contain a fatty acid metal salt. As the fatty acid metal salt, any known fatty acid metal salt can be used, but it is preferable to contain a poorly water-soluble fatty acid metal salt made of a divalent or higher polyvalent metal and a fatty acid. Specifically, known fatty acids can be used, including linear saturated fatty acids such as nonanoic acid, lauric acid, stearic acid, and behenic acid, linear unsaturated fatty acids such as oleic acid and linoleic acid, fatty acids having a branched structure such as 15-methylhexadecanoic acid, and fatty acids having other functional groups such as 2-hydroxydodecanoic acid and 12-hydroxystearic acid. The fatty acid preferably has a carbon number of 8 to 22, and more preferably has a carbon number of 12 to 20. When the carbon number is 8 or more, the affinity with the wax increases, and the dispersibility of the wax in the toner is improved, and when the carbon number is 22 or less, the low-temperature fixability can be improved. The metal may be any known metal, but is preferably at least one metal selected from the group consisting of Al, Mg, and Zn, and more preferably Al. The higher the valence and the smaller the ionic radius, the stronger the interaction with the oxygen atom site in resin A, and the better the dispersion of the wax in the toner.

[0044] When the content of the wax in the toner particles is A% by mass and the content of the fatty acid metal salt in the toner particles is B% by mass, the ratio of B to A (B / A) is preferably 0.0010 to 1.0000, more preferably 0.0100 to 0.1000, from the viewpoint of the fluidity and fixability of the toner. By making B / A 0.0010 or more, the dispersibility of the wax in the toner is improved, and the fluidity of the toner during long-term use is improved. By making B / A 1.0000 or less, the fixability is further improved.

[0045] Furthermore, when the content of the fatty acid metal salt in the toner particles is B% by mass and the content of the resin A in the toner particles is C% by mass, the ratio of B to C (B / C) is preferably 0.0100 to 10.0000, more preferably 0.1000 to 1.0000. By making B / C 0.0100 or more, the dispersibility of the wax in the toner is improved, and the fluidity of the toner during long-term use is improved. By making B / C 10.0000 or less, the bleeding of the fatty acid metal salt to the toner surface is further suppressed, and the fluidity of the toner is further improved.

[0046] Furthermore, when the number of moles of silicon atoms derived from the resin A in the toner particles is E and the number of moles of metal in the fatty acid metal salt in the toner particles is F, the ratio of E to F (E / F) is preferably 0.100 to 10,000, and more preferably 0.1000 to 6,000. It has been found that when E / F is in this range, the fluidity during long-term use is improved and the charge amount of the toner is uniform. The reason for this is that when E / F is in this range, the interaction between the fatty acid metal salt and the resin A is strong, and the toner has a high chargeability in the toner. It is believed that the dispersibility of the fatty acid metal salt is improved, resulting in a uniform charge amount of the toner. The number of moles of silicon atoms derived from resin A in the toner particles can be controlled by the type and amount of resin A used when producing the toner particles, and the type and amount of silane compound used when producing resin A. The number of moles of the metal in the fatty acid metal salt in the toner particles can be controlled by the type and amount of resin A during the production of the toner particles.

[0047] <Coloring agent> The toner particles may contain a colorant. The colorant is not particularly limited, and the following known colorants can be used. Examples of yellow pigments that can be used include condensed azo compounds such as yellow iron oxide, navel yellow, naphthol yellow S, Hansa yellow G, Hansa yellow 10G, benzidine yellow G, benzidine yellow GR, quinoline yellow lake, permanent yellow NCG, and tartrazine lake, isoindolinone compounds, anthraquinone compounds, azo metal complexes, methine compounds, and allylamide compounds. Specific examples include the following. CI Pigment Yellow 12, 13, 14, 15, 17, 62, 74, 83, 93, 94, 95, 109, 110, 111, 128, 129, 147, 155, 168, 180185. Examples of orange pigments include the following: Permanent Orange GTR, Pyrazolone Orange, Balkan Orange, Benzidine Orange G, Induthrene Brilliant Orange RK, Induthrene Brilliant Orange GK. Examples of red pigments include condensed azo compounds such as red iron oxide, permanent red 4R, lithol red, pyrazolone red, watching red calcium salt, lake red C, lake red D, brilliant carmine 6B, brilliant carmine 3B, eosin lake, rhodamine lake B, and alizarin lake, diketopyrrolopyrrole compounds, anthraquinone compounds, quinacridone compounds, basic dye lake compounds, naphthol compounds, benzimidazolone compounds, thioindigo compounds, and perylene compounds. Specific examples include the following. CI Pigment Red 2, 3, 5, 6, 7, 23, 48:2, 48:3, 48:4, 57:1, 81:1, 122, 144, 146, 166, 169, 177, 184, 185, 202, 206, 220, 221, 254. Examples of blue pigments include copper phthalocyanine compounds and their derivatives such as alkali blue lake, Victoria blue lake, phthalocyanine blue, metal-free phthalocyanine blue, phthalocyanine blue partial chloride, fast sky blue, and indanthrene blue BG, anthraquinone compounds, and basic dye lake compounds. Specific examples include the following. CI Pigment Blue 1, 7, 15, 15:1, 15:2, 15:3, 15:4, 60, 62, 66. Examples of purple pigments include Fast Violet B and Methyl Violet Lake. Examples of green pigments include Pigment Green B, Malachite Green Lake, and Final Yellow Green G. Examples of white pigments include zinc oxide, titanium oxide, antimony white, and zinc sulfide. Examples of black pigments include carbon black, aniline black, non-magnetic ferrite and magnetite, as well as pigments toned to black using the above-mentioned yellow, red and blue colorants. These colorants may be used alone or in combination of two or more. These colorants can also be used in the form of a solid solution. If necessary, the colorant may be surface-treated with a substance that does not inhibit polymerization. The content of the colorant in the toner particles is preferably 3.0% by mass to 15.0% by mass.

[0048] <Charge control agent> The toner particles may contain a charge control agent. There is no particular limitation on the charge control agent, and any known charge control agent may be used. In particular, a charge control agent that has a high charging speed and can stably maintain a constant charge amount is preferred. Furthermore, when the toner particles are produced by a direct polymerization method, a charge control agent that has low polymerization inhibition properties and is substantially free of solubilized matter in an aqueous medium is particularly preferred. As the charge control agent that controls the toner particles to have a negative charge, the following can be mentioned, for example. Organometallic compounds and chelating compounds include monoazo metal compounds, acetylacetone metal compounds, aromatic oxycarboxylic acids, aromatic dicarboxylic acids, oxycarboxylic acids and dicarboxylic acid-based metal compounds. Other examples include aromatic oxycarboxylic acids, aromatic mono- and polycarboxylic acids and their metal salts, anhydrides or esters, and phenol derivatives such as bisphenol. Further examples include urea derivatives, metal-containing salicylic acid compounds, metal-containing naphthoic acid compounds, boron compounds, quaternary ammonium salts, and calixarenes. On the other hand, examples of charge control agents that control the toner particles to be positively charged include the following. Nigrosine and nigrosine modifications such as fatty acid metal salts; guanidine compounds; imidazole compounds; onium salts such as quaternary ammonium salts such as tributylbenzylammonium-1-hydroxy-4-naphthosulfonate, tetrabutylammonium tetrafluoroborate, and their analogues such as phosphonium salts, and lake pigments thereof; triphenylmethane dyes and lake pigments thereof (lake agents include phosphotungstic acid, phosphomolybdic acid, phosphotungstomolybdic acid, tannic acid, lauric acid, gallic acid, ferricyanide, ferrocyanide, etc.); metal salts of higher fatty acids; resin-based charge control agents. These charge control agents can be used alone or in combination of two or more. The content of these charge control agents in the toner particles is preferably 0.01% by mass to 10% by mass.

[0049] <External additives> The toner particles can be used without adding any external additives. However, in order to improve the flowability, chargeability, cleaning properties, etc., so-called external additives such as a fluidizing agent and a cleaning aid may be added to the toner. Examples of the external additive include inorganic oxide fine particles such as silica fine particles, alumina fine particles, and titanium oxide fine particles, and inorganic titanate compound fine particles such as strontium titanate and zinc titanate. These may be used alone or in combination of two or more. The BET specific surface area of ​​the external additive is 10m 2 / g~450m 2 It is preferred that the molecular weight is / g. The BET specific surface area is determined by a low-temperature gas adsorption method using a dynamic constant pressure method in accordance with the BET multipoint method. Specifically, a specific surface area measuring device (product name: Gemini 2375 Ver. 5.0, manufactured by Shimadzu Corporation) is used to adsorb nitrogen gas onto the surface of the sample, and the BET multipoint method is used to measure the BET specific surface area (m 2 / g) is calculated. The total amount of these various external additives added is preferably 0.05 parts by mass to 10 parts by mass, more preferably 0.1 parts by mass to 5 parts by mass, based on 100 parts by mass of toner particles. Also, various external additives may be used in combination.

[0050] <Developer> The toner can be used as a magnetic or non-magnetic one-component developer, but may also be mixed with a carrier and used as a two-component developer. As the carrier, magnetic particles made of known materials such as metals such as iron, ferrite, magnetite, and alloys of these metals with metals such as aluminum and lead can be used. Of these, it is preferable to use ferrite particles. As the carrier, a coated carrier in which the surface of magnetic particles is coated with a coating agent such as resin, or a resin dispersion type carrier in which magnetic fine powder is dispersed in a binder resin can also be used. The carrier preferably has a volume average particle size of 15 μm to 100 μm, and more preferably 25 μm to 80 μm.

[0051] <About the manufacturing method of toner particles> The toner particles can be produced by known methods, such as a kneading and grinding method or a wet production method. From the viewpoint of uniform particle size and shape controllability, a wet production method is preferably used. Further, examples of the wet production method include a suspension polymerization method, a dissolution suspension method, an emulsion polymerization aggregation method, and an emulsion aggregation method.

[0052] Here, the suspension polymerization method will be described as an example. The suspension polymerization method may include a step of preparing a polymerizable monomer composition by uniformly dissolving or dispersing resin A, a polymerizable monomer for producing a binder resin, wax, a fatty acid metal salt, and, if necessary, other additives such as a colorant, using a dispersing machine such as a ball mill or an ultrasonic dispersing machine (a step of preparing a polymerizable monomer composition). At this time, if necessary, a multifunctional monomer, a chain transfer agent, a charge control agent, a plasticizer, and the like can be appropriately added.

[0053] Suitable examples of the polymerizable monomer in the suspension polymerization method include the vinyl polymerizable monomers shown below. Styrene; styrene derivatives such as α-methylstyrene, β-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, pn-butylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, pn-dodecylstyrene, p-methoxystyrene, and p-phenylstyrene; methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-amyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, n-nonyl acrylate, cyclohexyl acrylate, benzyl acrylate, dimethyl phosphate ethyl acrylate, diethyl phosphate ethyl acrylate, and dibutyl phosphate ethyl acrylate, 2-benzoyloxyethyl acrylate, and other acrylic polymerizable monomers; methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-amyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, n-octyl methacrylate, n-nonyl methacrylate, diethyl phosphate ethyl methacrylate, dibutyl phosphate ethyl methacrylate, and other methacrylic polymerizable monomers; methylene aliphatic monocarboxylic acid esters; vinyl esters such as vinyl acetate, vinyl propionate, vinyl benzoate, vinyl butyrate, vinyl benzoate, and vinyl formate; vinyl ethers such as vinyl methyl ether, vinyl ethyl ether, and vinyl isobutyl ether; vinyl methyl ketone, vinyl hexyl ketone, and vinyl isopropyl ketone.

[0054] In the suspension polymerization method, the polymerizable monomer composition is introduced into a previously prepared aqueous medium, and droplets of the polymerizable monomer composition are formed by a stirrer or disperser having a high shear force. It may also have a step of forming toner particles into a desired size (granulation step). It is preferable that the aqueous medium in the granulation process contains a dispersion stabilizer in order to control the particle size of the toner particles, to sharpen the particle size distribution, and to suppress the coalescence of the toner particles during the manufacturing process. Dispersion stabilizers are generally broadly classified into polymers that exhibit repulsive force due to steric hindrance and poorly water-soluble inorganic compounds that stabilize dispersion by electrostatic repulsive force. Fine particles of poorly water-soluble inorganic compounds are preferably used because they dissolve in acid or alkali and can be easily removed by washing with acid or alkali after polymerization.

[0055] As the dispersion stabilizer of the poorly water-soluble inorganic compound, one containing any one of magnesium, calcium, barium, zinc, aluminum, and phosphorus is preferably used. More preferably, one containing any one of magnesium, calcium, aluminum, and phosphorus. Specific examples thereof include the following. Sodium phosphate, magnesium phosphate, tricalcium phosphate, aluminum phosphate, zinc phosphate, magnesium carbonate, calcium carbonate, magnesium hydroxide, calcium hydroxide, aluminum hydroxide, calcium metasilicate, calcium sulfate, barium sulfate, calcium chloride, hydroxyapatide. The above dispersion stabilizers may be used in combination with organic compounds such as polyvinyl alcohol, gelatin, methyl cellulose, methylhydroxypropyl cellulose, ethyl cellulose, sodium salt of carboxymethyl cellulose, and starch. The dispersion stabilizer is preferably used in an amount of 0.01 to 2.00 parts by mass based on 100 parts by mass of the polymerizable monomer.

[0056] Furthermore, in order to make these dispersion stabilizers finer, 0.001 to 0.1 parts by mass of a surfactant may be used in combination with 100 parts by mass of the polymerizable monomer. Specifically, commercially available nonionic surfactants, commercially available anionic surfactants, and commercially available cationic surfactants can be used. For example, sodium dodecyl sulfate, sodium tetradecyl sulfate, sodium pentadecyl sulfate, sodium octyl sulfate, sodium oleate, sodium laurate, potassium stearate, calcium oleate, etc. are preferably used.

[0057] The suspension polymerization method may include a step (polymerization step) of obtaining a toner base particle dispersion by polymerizing the polymerizable monomer contained in the polymerizable monomer composition at a temperature of preferably 50° C. to 90° C. The polymerization step may be performed after the granulation step or may be performed during the granulation step. In the polymerization step, it is preferable to carry out a stirring operation so that the temperature distribution in the vessel is uniform. When a polymerization initiator is added, it can be added at any timing and for any required time. In addition, the temperature may be raised in the latter half of the polymerization reaction in order to obtain a desired molecular weight distribution, and further, in order to remove unreacted polymerizable monomers, by-products, etc. from the system, a part of the aqueous medium may be distilled off by a distillation operation in the latter half of the reaction or after the reaction is completed. The distillation operation can be carried out under normal pressure or reduced pressure.

[0058] In the suspension polymerization method, an oil-soluble initiator is generally used. Examples of the initiator include the following: Azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis-4-methoxy-2,4-dimethylvaleronitrile; acetylcyclohexylsulfonyl peroxide, diisopropyl peroxycarbonate, decanonyl peroxide, lauroyl peroxide, stearoyl peroxide, propionyl peroxide, acetyl peroxide, tert-butylperoxy-2-ethylhexanoate, benzoyl peroxide, tert-butylperoxyisobutyrate, cyclohexanone peroxide, methyl ethyl ketone peroxide, dicumyl peroxide, tert-butyl hydroperoxide, di-tert-butyl peroxide initiators such as butyl peroxide, tert-butyl peroxypivalate, and cumene hydroperoxide;

[0059] The polymerization initiator may be used in combination with a water-soluble initiator as necessary, and examples thereof include the following. Ammonium persulfate, potassium persulfate, 2,2'-azobis(N,N'-dimethyleneisobutyromidine) hydrochloride, 2,2'-azobis(2-aminodinopropane) hydrochloride, azobis(isobutylamidine) hydrochloride, 2,2'-azobisisobutyronitrile sodium sulfonate, ferrous sulfate, or hydrogen peroxide. These polymerization initiators can be used alone or in combination of two or more. In order to control the degree of polymerization of the polymerizable monomer, it is also possible to further use a chain transfer agent, a polymerization inhibitor, etc. in combination.

[0060] The toner particle dispersion thus obtained is sent to a filtration step for solid-liquid separation of the toner particles and the aqueous medium. The solid-liquid separation for obtaining toner particles from the obtained toner particle dispersion can be carried out by a general filtration method, and then, in order to remove foreign matter that has not been completely removed from the toner particle surface, it is preferable to further wash the toner particles by reslurrying or washing with washing water. After sufficient washing, solid-liquid separation is again carried out to obtain a toner cake. Then, the toner is dried by a known drying means, and if necessary, a particle group having a particle size other than the specified particle size is separated by classification to obtain toner particles. The particle group having a particle size other than the specified particle size separated at this time may be reused to improve the final yield.

[0061] The toner particle size is preferably a weight average particle size (D4) of 3.0 μm to 10.0 μm in terms of obtaining a high-definition and high-resolution image. The weight average particle size (D4) of the toner is measured by a capillary electrical resistance method. Specifically, it is measured using a "Coulter Counter Multisizer 3" (manufactured by Beckman Coulter, Inc.).

[0062] The measurement methods for each physical property value are described below. <Separation of toner and additives> First, in the case where the surface of the toner particles has been treated with an external additive or the like, the external additive is removed by the following method to obtain the toner particles. Add 160 g of sucrose (Kishida Chemical) to 100 mL of ion-exchanged water and dissolve in a hot water bath to prepare a concentrated sucrose solution. Add 31 g of the concentrated sucrose solution and 6 mL of Contaminon N (a 10% aqueous solution of a pH 7 neutral detergent for cleaning precision measuring instruments, consisting of nonionic surfactants, anionic surfactants, and organic builders, manufactured by Wako Pure Chemical Industries, Ltd.) to a centrifuge tube (50 mL capacity) to prepare a dispersion. Add 1.0 g of toner to this dispersion and break up the toner clumps with a spatula or similar. The centrifuge tube is shaken in a shaker at 350 strokes per minute (spm) for 20 minutes. After shaking, the solution is transferred to a glass tube for a swing rotor (capacity 50 mL) and separated in a centrifuge (H-9R, manufactured by Kokusan Co., Ltd.) at 3500 rpm for 30 minutes. This operation separates the toner particles from the removed external additives. Visually check that the toner and the aqueous solution are sufficiently separated, and collect the toner that has separated to the top layer with a spatula. The collected toner is filtered through a vacuum filter, and then dried in a dryer for at least one hour to obtain toner particles. This operation is repeated several times to ensure the required amount.

[0063] <Method of extracting resin A from toner particles> Resin A in the toner particles is extracted by separating the extract using tetrahydrofuran (THF) using a solvent gradient elution method. The preparation method is shown below. 10.0 g of toner particles were weighed out and placed in a cylindrical filter paper (Toyo Roshi No. 84). The mixture is then placed in a filter extractor. Extraction is performed for 20 hours using 200 mL of THF as the solvent, and the solid obtained by removing the solvent from the extract is the THF-soluble fraction. The THF-soluble fraction contains resin A. This process is repeated several times to obtain the required amount of THF-soluble fraction. For the solvent gradient elution method, a gradient preparative HPLC (Shimadzu LC-20AP high pressure gradient preparative system, Waters SunFire preparative column 50mmφ250mm) is used. The column temperature is 30°C, the flow rate is 50mL / min, and the mobile phase uses acetonitrile as a poor solvent and THF as a good solvent. 0.02g of the THF soluble matter obtained by extraction is dissolved in 1.5mL of THF to prepare the sample for separation. The mobile phase starts with a composition of 100% acetonitrile, and 5 minutes after the sample injection, the ratio of THF is increased by 4% per minute, until the mobile phase composition becomes 100% THF over 25 minutes. The components can be separated by drying the obtained fraction. This allows for the production of resin A. Which fraction is resin A can be determined by measuring the silicon atom content and 13 This can be determined by C-NMR measurement. If necessary, the solvent gradient elution is repeated to obtain the required amount of resin A. The ratio of the mass of the obtained resin A to the mass of the toner particles used to extract the resin A is defined as the content C (mass %) of resin A in the toner particles.

[0064] <Method for measuring the content of silicon atoms in resin A> The content of silicon atoms in resin A is measured using a wavelength dispersive X-ray fluorescence analyzer "Axios" (PANalytical). The measurement conditions are set and the measurement data is analyzed using the accompanying dedicated software "SuperQ ver.4.0F" (PANalytical). The anode of the X-ray tube is Rh, and the acceleration voltage and current are 24 kV and 100 mA, respectively. The measurement atmosphere is vacuum, the measurement diameter (collimator mask diameter) is 27 mm, and the measurement time is 10 seconds. A proportional counter (PC) is used as the detector. The measurement is performed by measuring the count rate (unit: cps) of Si-Kα rays observed at a diffraction angle (2θ) = 109.08° when PET is used as the analyzing crystal, and calculating using the following calibration curve. As the measurement sample, resin A (or the resin represented by formula (1)) itself is used, or a resin extracted from toner particles by the above-mentioned extraction method is used. The pellets for measurement are made using a tablet molding and compression machine "BRE-32" (Maekawa Testing Machinery Manufacturing Co., Ltd.) 4 g of the measurement sample is placed in a dedicated aluminum ring for pressing, flattened, and pressed at 20 MPa for 60 seconds to form pellets with a thickness of 2 mm and a diameter of 39 mm. As pellets for creating a calibration curve to determine the content, binder [product name: Spectro Blend, components: C 81.0, O 2.9, H 13.5, N 2.6 (mass%), chemical formula: C 19 H 38 To 100 parts by mass of SiO2 (hydrophobic fumed silica) [product name: AEROSIL NAX50, specific surface area: 40±10, carbon content: 0.45-0.85%; manufactured by Nippon Aerosil Co., Ltd.], add 0.50 parts by mass of SiO2, mix thoroughly using a coffee mill, and mold into pellets. In the same manner, mix and mold into pellets so that the SiO2 amounts are 5.00 parts by mass, 10.00 parts by mass, and 15.00 parts by mass, respectively. A linear calibration curve is obtained by plotting the count rate of the obtained X-rays on the vertical axis and the concentration of Si added in each calibration sample on the horizontal axis. Next, the count rate of the Si-Kα ray is measured for the measurement sample in the same manner.Then, the content (mass%) of silicon atoms is obtained from the obtained calibration curve.The molar concentration of silicon atoms is calculated from the content of silicon atoms.

[0065] <Method for confirming the structure of Resin A (presence or absence of a silyl group substituent and the structure of the substituent)> The presence or absence of a silyl group substituent in Resin A and the structure of the substituent are as follows: 29 Si-NMR (solid Body) measurements, and 13 The measurement conditions are as follows: Resin A itself is used as a measurement sample, or the resin extracted from the toner particles by the above-mentioned extraction method is used.

[0066] ( 29 Si-NMR (solid state) measurement conditions Equipment: JEOL RESONANCE JNM-ECX500II Sample tube: 3.2mmφ Sample size: 150mg Measurement temperature: room temperature Pulse mode: CP / MAS Measurement nuclear frequency: 97.38MHz ( 29 Si) Reference material: DSS (external standard: 1.534ppm) Sample rotation speed: 10kHz Contact time: 10ms Delay time: 2s Number of times: 2000 to 8000 The above measurement allows the abundance ratio to be determined by peak separation and integration of multiple silane components according to the number of oxygen atoms bonded to silicon by curve fitting. In this way, the number of alkoxy groups or hydroxy groups in resin A can be confirmed.

[0067] ( 13 C-NMR (solid state) measurement conditions Equipment: JEOL RESONANCE JNM-ECX500II Sample tube: 3.2mmφ Sample size: 150mg Measurement temperature: room temperature Pulse mode: CP / MAS Measurement nuclear frequency: 123.25MHz ( 13 C) Reference substance: Adamantane (external standard: 29.5ppm) Sample rotation speed: 20kHz Contact time: 2ms Delay time: 2s Number of times accumulated: 1024 By the above measurement, various peaks are separated according to the type of the substituent of the silyl group in the resin A, and each peak is identified to determine the structure of each substituent.

[0068] <Confirmation of the structure of resin A (P 1 and L 1 )> P in Resin A 1 and L 1 The structure of 13 Confirm by C-NMR (solid state) measurement. The measurement conditions are as above ( 13 The measurement conditions are the same as those for C-NMR (solid). The measurement sample is resin A itself, or the resin extracted from the toner particles by the above-mentioned extraction method. By the above measurement, P in resin A 1 and L 1 The various peaks are separated according to the type of 1 and L 1 Determine the structure of.

[0069] <Method for extracting fatty acid metal salt from toner particles> 10.0 g of toner particles from which the external additives have been separated are weighed out, placed in a cylindrical filter paper (Toyo Roshi No. 84) and subjected to a Soxhlet extractor. Extraction is performed for 20 hours using 200 mL of THF as a solvent, and the THF-insoluble matter remaining on the cylindrical filter paper is dried to solidify. The resulting THF-insoluble matter is placed again in the cylindrical filter paper, and 200 mL of chloroform is added as a solvent in the Soxhlet extractor, extraction is performed for 8 hours, and the extract is concentrated and dried to separate the fatty acid metal salt from the toner particles. The operation is repeated as necessary to obtain the required amount of fatty acid metal salt. The ratio of the mass of the obtained fatty acid metal salt to the mass of the toner particles used to extract the fatty acid metal salt is defined as the content B (mass %) of the fatty acid metal salt in the toner particles.

[0070] <Confirmation of the type of metal in fatty acid metal salts in toner particles and measurement of molar concentration> After extracting the fatty acid metal salts by the above-mentioned method, the molar concentration of the metal is quantified using an inductively coupled plasma atomic emission spectrometer (ICP-AES (Seiko Instruments Inc.)). The type of the metal is also confirmed. As a pretreatment, 100.0 mg of fatty acid metal salt was added to 60% nitric acid (Kanto Chemical, atomic absorption spectrometry) (For use) Perform acid digestion using 8.00 ml. During acid decomposition, the sample is treated in a sealed container at an internal temperature of 220° C. for 1 hour using a microwave high-power sample pretreatment device ETHOS1600 (Milestone General Co., Ltd.) to prepare a solution sample containing polyvalent metal elements. Then, add ultrapure water to make the total amount 50.00g to prepare the measurement sample. A calibration curve is created for each metal element, and the amount of metal contained in the fatty acid metal salt is quantified. Also, confirm the type of metal contained in the fatty acid metal salt. The molar concentration of the metal in the fatty acid metal salt in the toner particles can be calculated from the ratio of the obtained metal amount to the mass of the toner particles used to extract the fatty acid metal salt.

[0071] <Method of measuring weight average molecular weight (Mw)> The weight average molecular weight (Mw) of a resin is measured by gel permeation chromatography (GPC) as follows. First, the sample is dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The resulting solution is then filtered through a solvent-resistant membrane filter "Myshoridisc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is prepared so that the concentration of components soluble in THF is approximately 0.8 mass%. This sample solution is used to perform measurements under the following conditions. Equipment: HLC8120 GPC (detector: RI) (Tosoh Corporation) Column: Shodex KF-801, 802, 803, 804, 805, 806, 807 (Showa Denko) Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Oven temperature: 40.0℃ Sample injection volume: 0.10 mL In calculating the molecular weight of the sample, a molecular weight calibration curve prepared using standard polystyrene resins (product names: "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", manufactured by Tosoh Corporation) is used.

[0072] <Method for measuring the acid value Av of resin> The acid value is the number of milligrams of potassium hydroxide required to neutralize the acid contained in 1 g of a sample. The acid value of a resin is measured in accordance with JIS K 0070-1992, and specifically, it is measured according to the following procedure. (1) Preparation of reagents Dissolve 1.0 g of phenolphthalein in 90 mL of ethyl alcohol (95% by volume), and add ion-exchanged water to make 100 mL to obtain a phenolphthalein solution. Dissolve 7 g of special grade potassium hydroxide in 5 mL of water and add ethyl alcohol (95% by volume) to make 1 L. Place in an alkali-resistant container to avoid contact with carbon dioxide, etc., leave for 3 days, then filter to obtain potassium hydroxide solution. Store the resulting potassium hydroxide solution in an alkali-resistant container. The factor of the potassium hydroxide solution is 25 mL of 0.1 mol / L hydrochloric acid in an Erlenmeyer flask. The amount of the potassium hydroxide solution required for neutralization is calculated by adding a few drops of the phenolphthalein solution to the solution and titrating it with the potassium hydroxide solution. The 0.1 mol / L hydrochloric acid used is prepared in accordance with JIS K 8001-1998. (2) Operation (A) Main Test Weigh out 2.0 g of the crushed sample into a 200 ml Erlenmeyer flask, add 100 ml of a toluene / ethanol (2:1) mixed solution, and dissolve for 5 hours. Next, add a few drops of the phenolphthalein solution as an indicator, and titrate with the potassium hydroxide solution. The end point of the titration is when the light red color of the indicator continues for about 30 seconds. (B) Blank test The titration is carried out in the same manner as above, except that no sample is used (i.e., only the toluene / ethanol (2:1) mixed solution is used). (3) The obtained result is substituted into the following formula to calculate the acid value. A = [(CB) × f × 5.61] / S Here, A is the acid value (mgKOH / g), B is the amount of potassium hydroxide solution added for the blank test (ml), C is the amount of potassium hydroxide solution added for the main test (ml), f is the factor of the potassium hydroxide solution, and S is the mass of the sample (g).

[0073] <Method for measuring the hydroxyl value (OHv) of resin> The hydroxyl value is the amount of potassium hydroxide (mg) required to neutralize the acetic acid bonded to the hydroxyl group when 1 g of a sample is acetylated. The hydroxyl value of a resin is measured according to JIS K 0070-1992, and more specifically, it is measured according to the following procedure. (1) Preparation of reagents Put 25 g of special grade acetic anhydride into a 100 mL measuring flask, add pyridine to make the total volume 100 mL, and shake thoroughly to obtain the acetylation reagent. Store the obtained acetylation reagent in a brown bottle to avoid contact with moisture, carbon dioxide, etc. Dissolve 1.0 g of phenolphthalein in 90 mL of ethyl alcohol (95% by volume), and add ion-exchanged water to make 100 mL to obtain a phenolphthalein solution. Dissolve 35 g of special grade potassium hydroxide in 20 mL of water and add ethyl alcohol (95% by volume) to make 1 L. Place in an alkali-resistant container to avoid contact with carbon dioxide, etc., leave for 3 days, then filter to obtain potassium hydroxide solution. Store the resulting potassium hydroxide solution in an alkali-resistant container. The factor of the potassium hydroxide solution is calculated by placing 25 mL of 0.5 mol / L hydrochloric acid in an Erlenmeyer flask, adding a few drops of the phenolphthalein solution, titrating with potassium hydroxide solution, and calculating the amount of potassium hydroxide solution required for neutralization. 0.5 mol / L hydrochloric acid prepared in accordance with JIS K 8001-1998 is used. (2) Operation (A) Main Test Weigh out 1.0 g of the ground sample into a 200 mL round-bottom flask, and add 5.0 mL of the acetylation reagent accurately using a volumetric pipette. If the sample is difficult to dissolve in the acetylation reagent, add a small amount of special grade toluene to dissolve it. Place a small funnel on the mouth of the flask and immerse about 1 cm of the bottom of the flask in a glycerin bath at about 97°C and heat it. At this time, it is preferable to cover the base of the neck of the flask with a piece of cardboard with a round hole in it to prevent the temperature of the neck of the flask from rising due to the heat of the bath. After 1 hour, remove the flask from the glycerin bath and allow it to cool. After allowing it to cool, add 1 mL of water through the funnel and shake to hydrolyze the acetic anhydride. To further complete the hydrolysis, heat the flask again in the glycerin bath for 10 minutes. After allowing it to cool, wash the funnel and the walls of the flask with 5 mL of ethyl alcohol. Add a few drops of the phenolphthalein solution as an indicator and titrate with the potassium hydroxide solution. The end point of the titration is when the light red color of the indicator continues for about 30 seconds. (B) Blank test The titration is carried out in the same manner as above, except that no sample is used. (3) The obtained result is substituted into the following formula to calculate the hydroxyl value. A = [{(BC) × 28.05 × f} / S] + D Here, A: hydroxyl value (mgKOH / g), B: amount of potassium hydroxide solution added for the blank test (mL), C: amount of potassium hydroxide solution added for the main test (mL), f: factor of the potassium hydroxide solution, S: mass of the sample (g), and D: acid value of the sample (mgKOH / g).

[0074] <Method of extracting wax from toner particles> The wax is extracted from the toner particles by separating it from the toner using Soxhlet extraction, as described below. 10.0 g of toner particles are weighed out, placed in a cylindrical filter paper (Toyo Roshi No. 84) and subjected to a Soxhlet extractor. Extraction is performed for 20 hours using 200 ml of hexane as a solvent, and the solvent is removed from the extract to obtain the wax of the toner particles.

[0075] <How to check the wax structure> The structure of the wax was determined by nuclear magnetic resonance spectroscopy ( 1 The compound is characterized using H-NMR (400 MHz, CDCl3, room temperature (25 °C)). Measuring device: FT NMR device JNM-EX400 (manufactured by JEOL Ltd.) Measurement frequency: 400MHz Pulse condition: 5.0μs Frequency range: 10500Hz Number of times accumulated: 64

[0076] <Measuring method for wax melting point> The melting point of the wax is measured using a differential scanning calorimeter "Q1000" (manufactured by TA Instruments) in accordance with ASTM D3418-82. The melting points of indium and zinc are used for temperature correction of the device detection section, and the heat of fusion of indium is used for heat correction. Specifically, 5 mg of sample is weighed out and placed in a silver pan. An empty silver pan is used as a reference, and one measurement is performed at a temperature rise rate of 10°C / min from the measurement start temperature of 20°C to the measurement end temperature of 180°C. The peak temperature of the maximum endothermic peak of the DSC curve in the temperature range of 20°C to 180°C during this first temperature rise is determined. The peak temperature of the maximum endothermic peak is taken as the melting point (°C).

[0077] <Measurement of wax content> The wax content in the toner particles is measured in the same manner using the above-mentioned differential scanning calorimeter. Specifically, first, the amount of heat absorbed by the wax alone is measured. 1 mg of the wax extracted from the toner particles using the above method is precisely weighed out and placed in an aluminum pan, with an empty aluminum pan used as a reference. The temperature is increased from 0°C to 150°C at a rate of 10°C / min and maintained at 150°C for 5 minutes. After that, it is cooled from 150°C to 0°C at a rate of 10°C / min. After maintaining at 0°C for 5 minutes, it is heated from 0°C to 150°C at a rate of 10°C / min. The endothermic heat ΔH1 (J / g) of the endothermic peak in the DSC curve at this time is taken as the endothermic heat of the wax alone. Next, the amount of heat absorbed by the toner particles is measured. 1 mg of toner particles is precisely weighed and placed in an aluminum pan, and an empty aluminum pan is used as a reference. The temperature is raised from 0°C to 150°C at a rate of 10°C / min, and the amount of heat absorbed ΔH2 (J / g) at the endothermic peak in the DSC curve at this time is taken as the amount of heat absorbed by the toner particles. From the heat absorption amount of the wax alone and the heat absorption amount of the toner particles measured by the above method, the following formula is obtained: The wax content in the toner particles is measured. Wax content in toner particles A (mass%) = ΔH2 / ΔH1 × 100 EXAMPLES

[0078] The present disclosure will be specifically described below with reference to examples, but the present disclosure is not limited to these examples. Unless otherwise specified, the "parts" of each material in the examples and comparative examples are all based on mass.

[0079] <Production example of styrene acrylic resin (R-1)> A styrene-acrylic resin (R-1) was produced according to the following procedure. 100.0 parts of propylene glycol monomethyl ether was heated while replacing with nitrogen, and refluxed at a liquid temperature of 120° C. or higher. A mixture of 83.4 parts of styrene, 20.9 parts of n-butyl acrylate, and 1.0 part of acrylic acid as polymerizable monomers, and 0.6 parts of tert-butyl peroxybenzoate [organic peroxide polymerization initiator, manufactured by NOF Corporation, product name: Perbutyl Z] as a polymerization initiator was added dropwise thereto over a period of 3 hours. After the dropwise addition was completed, the solution was stirred for 3 hours, and then distilled at normal pressure while increasing the liquid temperature to 170° C. After the liquid temperature reached 170° C., the pressure was reduced to 1 hPa, and distillation was performed for 1 hour to remove the solvent, obtaining a resin solid. The resin solid was dissolved in tetrahydrofuran, reprecipitated with n-hexane, and the precipitated solid was filtered to obtain a styrene-acrylic resin (R-1). The resulting styrene-acrylic resin (R-1) had an acid value of 10.6 mgKOH / g and a weight average molecular weight (Mw) of 13,000.

[0080] <Production example of styrene acrylic resin (R-2)> In the production example of styrene-acrylic resin (R-1), the polymer monomer was changed to 82.0 parts of styrene, 10.0 parts of methacrylic acid, and 8.0 parts of acrylic acid, and the amount of the polymerization initiator was changed to 1.0 part, respectively. In the same manner as in the production example of styrene-acrylic resin (R-1), styrene-acrylic resin (R-2) was obtained. The resulting styrene-acrylic resin (R-2) had an acid value of 161.0 mgKOH / g and a weight average molecular weight (Mw) of 46,000.

[0081] <Production example of acrylic resin (R-3)> Acrylic resin (R-3) was obtained in the same manner as in the production example of styrene-acrylic resin (R-1), except that the polymer monomer was changed to 30.0 parts of methyl methacrylate and 50.4 parts of acrylic acid, and the amount of polymerization initiator was changed to 1.0 part. The resulting acrylic resin (R-3) had an acid value of 351.0 mgKOH / g and a weight average molecular weight (Mw) of 8,700.

[0082] <Production example of polyester resin (R-4)> A polyester resin (R-4) was produced according to the following procedure. The following materials were charged into an autoclave equipped with a pressure reducing device, a water separating device, a nitrogen gas introducing device, a temperature measuring device, and a stirrer, and a reaction was carried out under a nitrogen atmosphere at normal pressure and 200°C for 5 hours. Bisphenol A-propylene oxide 2.1 mole adduct: 39.6 parts Terephthalic acid: 8.0 parts Isophthalic acid: 7.6 parts Tetrabutoxytitanate: 0.1 parts Thereafter, 0.01 parts of trimellitic acid and 0.12 parts of tetrabutoxy titanate were added, and the mixture was reacted at 220° C. for 3 hours, and then reacted under reduced pressure of 10 mmHg to 20 mmHg for 2 hours to obtain a polyester resin (R-4). The resulting polyester resin (R-4) had an acid value of 6.1 mgKOH / g and a weight average molecular weight (Mw) of 10,200.

[0083] <Synthesis of polyester resin (R-5)> Poly(ε-caprolactone) having a stearyl ester at the carboxylic acid terminal [(polyester resin (R-5)]] was synthesized by the following procedure. The following materials were charged into a reaction vessel equipped with a nitrogen gas inlet device, a temperature measuring device, and a stirrer, and the reaction was carried out at 100° C. for 5 hours under a nitrogen atmosphere. Stearyl alcohol: 3.0 parts ε-caprolactone: 38.2 parts Titanium(IV) tetraisopropoxide: 0.5 parts The obtained resin was dissolved in chloroform, and the solution was dropped into methanol for reprecipitation and filtration to obtain a polyester resin (R-5). The resulting polyester resin (R-5) had an acid value of 0.0 mgKOH / g, a hydroxyl value of 30.3 mgKOH / g, and Mw=8,300.

[0084] <Synthesis of polyester resin (R-6)> Polylactic acid [(polyester resin (R-6)] was synthesized according to the following procedure. The following materials were charged into an autoclave equipped with a pressure reducing device, a water separating device, a nitrogen gas introducing device, a temperature measuring device, and a stirrer, and a reaction was carried out under a nitrogen atmosphere at normal pressure and 200°C for 5 hours. Lactic acid: 100.0 parts Tetrabutoxytitanate: 0.1 parts Then, 0.1 parts of tetrabutoxy titanate was added, and the mixture was reacted at 220°C for 3 hours, and then reacted under reduced pressure of 10 mmHg to 20 mmHg for 2 hours. The obtained resin was dissolved in chloroform, and the solution was dropped into ethanol for reprecipitation and filtration to obtain polyester resin (R-6). The resulting polyester resin (R-6) had an acid value of 3.5 mgKOH / g and Mw=30,000.

[0085] <Production Example of Resin A> <Production Example of Resin (A-1)> Resin (A-1) represented by formula (1) was produced according to the following procedure. 200.00 parts of N,N-dimethylacetamide, 1 50.00 parts of styrene acrylic resin (R-1) was dissolved as the polymer portion, and 1.20 parts of 3-aminopropyltriethoxysilane as a silane compound, 2.87 parts of triethylamine, and 2.88 parts of DMT-MM [4-(4,6-dimethoxy-1,3,5-triazin-2-yl)-4-methylmorpholinium chloride] as a condensation agent were added, and the mixture was stirred at room temperature for 5 hours. After the reaction was completed, the solution was dropped into methanol, reprecipitated, and filtered to obtain resin (A-1). The weight average molecular weight Mw of resin (A-1) was 13,200.

[0086] <Production Examples of Resins (A-2) to (A-5) and (A-9) to (A-17)> In the production example of resin (A-1), P 1 Resins (A-2) to (A-5) and (A-9) to (A-17) were obtained in the same manner except that the type of (polymer portion); the type and amount of silane compound; and the amount of triethylamine and DMT-MM added were changed as shown in Table 1.

[0087] <Production Example of Resin (A-6)> Resin (A-5) 10.0 parts was dissolved in toluene 90.0 parts, mixed with pure water 400.0 parts, and stirred, and the pH was adjusted to 4.0 with dilute hydrochloric acid, and stirred at room temperature for 10.8 hours, and then the stirring was stopped and the mixture was transferred to a separatory funnel to extract the oil phase. The oil phase was concentrated and reprecipitated with methanol to obtain resin (A-6) represented by formula (1). The obtained resin (A-6) 29 Analysis by Si-NMR (solid state) measurement revealed that the compound had the formula R in (1) 1 ~R 3 were all hydroxy groups.

[0088] <Production Example of Resin (A-7)> Resin (A-7) was produced according to the following procedure. 50.00 parts of polyester resin (R-4) was dissolved in 500.00 parts of chloroform, and 0.74 parts of 3-isocyanatepropyltriethoxysilane, 1.65 parts of triethylamine, and 0.50 parts of titanium (IV) tetraisopropoxide were added under a nitrogen atmosphere and stirred at room temperature for 5 hours. After the reaction was completed, the solution was dropped into methanol, reprecipitated, and filtered to obtain resin (A-7).

[0089] <Production example of resin (A-8)> Resin (A-8) was synthesized in the same manner as in the production example of resin (A-7), except that polyester resin (R-4) was changed to polyester resin (R-5) and the amount of 3-isocyanatepropyltriethoxysilane added was changed from 0.74 parts to 6.61 parts.

[0090] <Production example of resin (A-18)> Diphenylmethane diisocyanate (MDI) 41.3 parts Bisphenol A ethylene oxide 2 mole adduct (BPA-2EO) 33.8 parts Tetrahydrofuran (THF) 300.0 parts The above materials were charged into a reaction vessel equipped with a stirrer and a thermometer while replacing the atmosphere with nitrogen. The mixture was heated to 50°C and subjected to a urethane reaction for 8 hours. After that, 3-isocyanate propyl 1.0 parts of 1-triethoxysilane was added and the reaction was continued for another 8 hours, and 3.0 parts of t-butyl alcohol was added to modify the isocyanate terminal. The solvent THF was distilled off to obtain resin (A-18). The weight average molecular weight Mw of resin (A-18) was 23,500.

[0091] [Table 1] The physical properties of the resulting resins (A-1) to (A-18) are shown in Table 2.

[0092] [Table 2]

[0093] <Production Example of Toner Particle 1> Into a reaction vessel, 390.0 parts of ion-exchanged water and 14.0 parts of sodium phosphate (12-hydrate) (manufactured by Rasa Kogyo Co., Ltd.) were added, and the mixture was kept at 65°C for 1.0 hours while being purged with nitrogen. Next, an aqueous calcium chloride solution in which 9.2 parts of calcium chloride (dihydrate) was dissolved in 10.0 parts of ion-exchanged water was added all at once using a TK homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.) while stirring at 12,000 rpm, to prepare an aqueous medium containing a dispersion stabilizer. Furthermore, hydrochloric acid was added to the aqueous medium to adjust the pH to 6.0, and an aqueous medium 1 was obtained. On the other hand, the following materials were placed in an attritor (manufactured by Nippon Coke & Engineering Co., Ltd.), and then zirconia particles having a diameter of 1.7 mm were added and dispersed at 220 rpm for 5.0 hours. After that, the zirconia particles were removed to prepare Dispersion 1 in which the colorant was dispersed. Styrene 60.0 parts Colorant (CI Pigment Blue 15:3) 6.5 parts Next, the following materials were added to the prepared dispersion liquid 1. Styrene 15.0 parts ・25.0 parts n-butyl acrylate Polyester resin (R-4) 4.0 parts Resin A (A-1) 0.5 parts Aluminum distearate 0.2 parts Divinylbenzene 0.3 parts Wax (ethylene glycol distearate: melting point 76°C) 12.0 parts The mixture was kept at 65° C. and uniformly dissolved and dispersed using a TK homomixer at 500 rpm to prepare a polymerizable monomer composition 1. While maintaining the temperature of the aqueous medium 1 at 70° C. and the rotation speed of the stirring device at 12,000 rpm, the polymerizable monomer composition 1 was charged into the aqueous medium 1, and 9.0 parts of t-butyl peroxypivalate was added as a polymerization initiator. Granulation was continued for 10 minutes while maintaining the stirring speed at 12,000 rpm. The stirring device was changed to a stirrer equipped with a propeller stirring blade, and polymerization was carried out for 5.0 hours while stirring at 150 rpm and maintaining the temperature at 70°C. The temperature was then further increased to 85°C and maintained at this temperature for 2.0 hours, and then cooled to room temperature, thereby obtaining toner particle dispersion 1. Hydrochloric acid was added to the obtained toner particle dispersion liquid 1 to adjust the pH to 1.4 or less, and the dispersion stabilizer was dissolved therein. The resulting mixture was filtered, washed, and dried to obtain toner particles 1.

[0094] <Production Examples of Toner Particles 2 to 37 and 42 to 44> In the same manner as in the production example of toner particle 1, except that the materials added to dispersion liquid 1 were changed as shown in Table 3, toner particles 2 to 37 and 42 to 44 were produced.

[0095] [Table 3]

[0096] <Production Example of Toner Particle 38> 660.0 parts of ion-exchanged water and 25.0 parts of a 48.5% aqueous solution of sodium dodecyldiphenyletherdisulfonate were mixed and stirred at 10,000 rpm using a TK homomixer to prepare an aqueous medium 2. The following materials were added to 500.0 parts of ethyl acetate and dissolved at 100 rpm with a propeller stirrer to prepare a solution. Styrene / butyl acrylate copolymer 100.0 parts (Copolymerization mass ratio: 80 / 20) Resin A (A-1) 0.5 parts Aluminum distearate 0.2 parts Polyester resin (R-4) 4.0 parts Colorant (CI Pigment Blue 15:3) 6.5 parts Wax (ethylene glycol distearate: melting point 76°C) 12.0 parts 150.0 parts of the aqueous medium 2 was placed in a vessel and stirred at 12,000 rpm using a TK homomixer, and 100.0 parts of the above-mentioned solution was added thereto and mixed for 10 minutes to prepare an emulsified slurry. Thereafter, 100.0 parts of the emulsified slurry was placed in a flask equipped with a degassing pipe, a stirrer, and a thermometer, and the solvent was removed under reduced pressure at 30° C. for 12 hours with stirring at 500 rpm, and then aged at 45° C. for 4 hours to obtain a solvent-free slurry. The solvent-removed slurry was filtered under reduced pressure, and then 300.0 parts of ion-exchanged water was added to the resulting filter cake, which was then mixed and redispersed in a TK homomixer (at a rotation speed of 12,000 rpm for 10 minutes), and then filtered. The obtained filter cake was dried in a dryer at 45° C. for 48 hours, and sieved through a mesh with an opening of 75 μm to obtain toner particles 38.

[0097] <Production Example of Toner Particle 39> (Production of dispersion of binder resin particles) To 200 parts of toluene (manufactured by Wako Pure Chemical Industries), 60 parts of ethylene vinyl acetate resin (manufactured by Tosoh: Ultrathene 685), 0.5 parts of resin A (A-1), and 0.2 parts of aluminum distearate were added, heated to 90°C, and then stirred for 3 hours to dissolve. To the toluene solution in which ethylene vinyl acetate resin, resin A, and aluminum distearate were dissolved, 6 parts of anionic surfactant (Neogen RK, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 180 parts of ion-exchanged water in which 3 parts of anionic surfactant (NonSal LN1, manufactured by Nippon Oil & Fats Co., Ltd.) were added. Then, the mixture was thoroughly stirred at 4000 rpm using an ultra-high speed stirring device TK Robomix (manufactured by Primix Co., Ltd.). After that, the mixture was dispersed for about 1 hour using a high-pressure impact type dispersing machine Nanomizer (manufactured by Yoshida Kikai Kogyo Co., Ltd.), and then the toluene was removed using an evaporator, and the mixture was adjusted with ion-exchanged water to obtain a dispersion of binder resin fine particles with a solid content concentration of 28%. (Production of dispersion of wax particles) Wax (ethylene glycol distearate: melting point 76°C) 20.0 parts Anionic surfactant (Daiichi Kogyo Seiyaku: Neogen RK) 1.0 part 79.0 parts of ion-exchanged water The above formulation was placed in a mixing vessel equipped with an agitator, heated to 90°C, and circulated through a Clearmix W Motion (manufactured by M Technique) while stirring at a shear mixing section with a rotor outer diameter of 3 cm and a clearance of 0.3 mm at a rotor rotation speed of 19,000 r / min and a screen rotation speed of 19,000 r / min. After dispersing for 60 minutes, it was cooled to 40°C under cooling treatment conditions of a rotor rotation speed of 1,000 r / min, screen rotation speed of 0 r / min, and a cooling rate of 10°C / min, and the mixture was adjusted with ion exchanged water to obtain a dispersion of wax microparticles with a solids concentration of 20%. (Production of pigment dispersion) CI Pigment Blue 15:3 10.0 parts 78.0 parts of ion-exchanged water Anionic surfactant (Daiichi Kogyo Seiyaku: Neogen RK) 2.0 parts The above materials were mixed, then dispersed for 1 hour using a high-pressure impact disperser Nanomizer (manufactured by Yoshida Kikai Kogyo Co., Ltd.), and adjusted with ion-exchanged water to prepare a pigment dispersion with a solids concentration of 10%. (Production of toner particles) Dispersion of binder resin particles (solid content 28%) 320.0 parts Pigment dispersion (10% solids) 50.0 parts Wax microparticle dispersion (20% solids) 75.0 parts The above materials were put into a round stainless steel flask and mixed. An aqueous solution of 8 parts of magnesium sulfate dissolved in 98 parts of ion-exchanged water was added thereto, and dispersed for 10 minutes at 5000 r / min using a homogenizer (IKA Ultra Turrax T50). After that, the mixture was heated to 50°C in a heating water bath using a stirring blade while appropriately adjusting the rotation speed so that the mixture was stirred. After holding at 50°C for 1 hour, the weight average particle size (D4) of the formed aggregated particles was measured. As a result, it was confirmed that aggregated particles with a weight average particle size (D4) of about 6.0 μm were formed. To the dispersion of the obtained aggregated particles, an aqueous solution in which 40 parts of sodium ethylenediaminetetraacetate was dissolved in 360 parts of ion-exchanged water was added, and then 2800 parts of ion-exchanged water was further added. The mixture was heated to 80°C while continuing to stir, and kept in a sealed state for 2 hours to obtain sufficiently fused particles. After that, the mixture was filtered and separated into solid and liquid, and the filtered matter was thoroughly washed with ion-exchanged water and dried using a vacuum dryer to obtain toner particles 39 having a weight average particle size (D4) of 6.7 μm.

[0098] <Production Example of Toner Particle 40> (Production of polyester resin (R-7)) The following materials were charged into a reaction vessel equipped with a nitrogen inlet tube, a dehydration tube, a stirrer and a thermocouple, and mixed with stirring to prepare a monomer solution. Terephthalic acid 65.0 parts Bisphenol A-propylene oxide 2 mol adduct 100.0 parts To the monomer solution, 1.5 parts of dibutyltin was added as a catalyst relative to 100 parts of the total amount of monomers. Next, the temperature was quickly raised to 180°C under normal pressure in a nitrogen atmosphere, and then the mixture was heated from 180°C to 210°C at a rate of 10°C / hour to distill off water to carry out polycondensation. After the temperature reached 210°C, the pressure in the reaction tank was reduced to 5 kPa or less, and polycondensation was carried out under conditions of a temperature of 210°C and 5 kPa or less to obtain a polyester resin (R-7). At that time, the polymerization time was adjusted so that the softening point of the resulting polyester resin (R-7) would be 115°C. (Production of toner particles) Polyester resin (R-7) 90.0 parts Polyester resin (R-4) 10.0 parts CI Pigment Blue 15:3 6.5 parts Resin A (A-1) 0.5 parts Aluminum distearate 0.2 parts Wax (ethylene glycol distearate: melting point 76°C) 12.0 parts The above materials were mixed in a Henschel mixer (FM-75, manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), and then mixed in a twin-screw mixer (PCM-30, manufactured by Ikegai Iron Works Co., Ltd.) at a rotation speed of 3.3 s. -1 The mixture was mixed at a mixing temperature of 120°C. The mixed mixture was cooled and coarsely pulverized to 1 mm or less using a hammer mill to obtain a coarsely pulverized product. The coarsely pulverized product was finely pulverized using a mechanical pulverizer (T-250 manufactured by Turbo Kogyo Co., Ltd.). The finely pulverized powder was further classified using a multi-division classifier utilizing the Coanda effect to obtain toner particles 40 having a weight average particle size (D4) of 7.5 μm.

[0099] <Production Example of Toner Particle 41> Toner particles 41 are obtained in the same manner as in the production example of toner particles 40, except that Resin A (A-1) in the production example of toner particles 40 is changed to Resin A (A-17).

[0100] <Production Examples of Toners 1 to 44> For 100.0 parts of each of the obtained toner particles 1 to 44, the BET value was 200 m 2 / g and 0.6 parts of hydrophobic silica fine particles having a number average particle size of 8 nm were mixed in a Henschel mixer (manufactured by Mitsui Miike Chemical Engineering Co., Ltd.), and sieved through a mesh with 150 μm openings to obtain toners 1-44. The physical properties of the obtained toners 1 to 44 are shown in Table 6.

[0101] [Table 4] P 1 : Polymer moiety in formula (1) in resin A B / A: fatty acid metal salt content B (mass%) / wax content A (mass%) B / C: fatty acid metal salt content B (mass%) / resin A content C (mass%) E / F: number of moles of silicon atoms derived from resin A E / number of moles of metal in fatty acid metal salt F

[0102] [Examples 1 to 41, Comparative Examples 1 to 3] The methods for evaluating each of the toners 1 to 44 are described below. The evaluation results are shown in Table 5.

[0103] <Evaluation of low-temperature fixability> The image forming device is a color laser printer (HP Color A modified HP LaserJet 3525dn (HP LaserJet 3525dn) was prepared, the toner was removed from the cyan cartridge, and the toner to be evaluated was filled in place of the cyan cartridge. Next, the receiving paper (HP Laser Jet 90, HP Laser Jet 3525dn, HP Laser Jet 3525dn) was 2 ) using the filled toner, an unfixed toner image of 2.0 cm length x 15.0 cm width (toner loading amount: 0.9 mg / cm 2 ) was formed at a position 1.0 cm from the upper end in the paper feed direction. Next, the removed fixing unit was modified so that the fixing temperature and process speed could be adjusted, and a fixing test of an unfixed image was carried out using this. First, in a normal temperature and humidity environment (temperature 23°C, relative humidity 60%), the process speed was set to 360 mm / s, and the initial temperature was 140°C, and the set temperature was increased in increments of 5°C, while the unfixed image was fixed at each temperature. The evaluation criteria for low-temperature fixability are as follows. The low-temperature fixation start point is the lowest temperature at which the low-temperature offset phenomenon (the phenomenon in which part of the toner adheres to the fixing device) is not observed. (Evaluation Criteria) A: The low temperature side fixing start point is less than 160℃ B: The low-temperature side fixing start point is 160°C or higher and less than 180°C. C: The low temperature side fixing start point is 180℃ or higher and less than 195℃ D: The low-temperature side fixing start point is 195°C or higher and less than 210°C. E: The low temperature side fixing start point is 215℃ or higher In the present disclosure, ranks A to C were determined to be good low-temperature fixability.

[0104] <Evaluation of hot offset resistance> The image forming device is a color laser printer (HP Color A modified HP LaserJet 3525dn (HP LaserJet 3525dn) was prepared, the toner was removed from the cyan cartridge, and the toner to be evaluated was filled in place of the cyan cartridge. Next, the receiving paper (HP Laser Jet 90, HP Laser Jet 3525dn, HP Laser Jet 3525dn) was 2 ) using the filled toner, an unfixed toner image of 2.0 cm length x 15.0 cm width (toner loading amount: 0.9 mg / cm 2 ) was formed at a position 1.0 cm from the upper end in the paper feed direction. Next, the removed fixing unit was modified so that the fixing temperature and process speed could be adjusted, and a fixing test of an unfixed image was carried out using this. In a normal temperature and humidity environment (23° C., 60% RH), the process speed was set to 360 mm / s, the initial temperature was 195° C., and the set temperature was successively increased by 5° C. at each temperature while fixing the unfixed image at each temperature. The evaluation criteria for hot offset resistance are as follows: The maximum fixing temperature is the maximum temperature at which the phenomenon (hot offset) in which molten toner adheres to the fixing roller is not observed. (Evaluation Criteria) A: The upper fixing temperature is 230°C or higher. B: The upper limit of the fixing temperature is 220°C or higher and 225°C or lower. C: The upper limit of the fixing temperature is 210°C or higher and 215°C or lower. D: The upper limit of the fixing temperature is 200°C or higher and 205°C or lower. E: The upper limit of the fixing temperature is 195°C or less. In the present disclosure, ranks A to C were determined to be good offset resistance.

[0105] <Evaluation of fluidity (solid conformability) during long-term use> In order to evaluate the fluidity of the toner, the solid image conformability was evaluated by the following method: The higher the fluidity of the toner, the better the solid image conformability. A modified HP Color LaserJet Enterprise CP4525dn (manufactured by HP), a commercially available laser printer, was used to print a toner image on Canon color laser copier paper with a toner load of 0.40 (mg / cm 2 ) was output at a fixing temperature of 190° C. and a process speed of 360 mm / sec. In a low temperature and low humidity environment (15°C, 10% RH), three full solid images were printed in succession as sample images. Then, 20,000 images with a print rate of 0.5% were printed with a 2-second intermittent time for every two images. In order to isolate the effect of component contamination, the drum unit was replaced with a new one, and three full solid images similar to the initial one were printed in succession. The solid tracking ability of the third full solid image obtained was evaluated by visual inspection. Solid tracking ability (Evaluation Criteria) A: Image density is uniform and not uneven. B: Image density is slightly uneven C: Image density is uneven, but not at a level that causes problems in use. D: The image density is uneven and the solid image is not uniform. E: The image density is blurred and the image is not uniform. In this disclosure, ranks A to C were determined to be good fluidity.

[0106] <Evaluation of dot reproducibility> The dot reproducibility was evaluated using the same evaluation device as in the evaluation of the solid followability, with a toner loading amount of 0.40 (mg / cm 2 ) on the following recording medium. 2 The image was output at a fixing temperature of 190°C and a process speed of 360mm / sec. The uniform charge of the toner improves dot reproducibility. After continuously printing 10,000 sheets of an A4 test pattern with a printing rate of 1% in a high temperature and high humidity environment (30°C, 85% RH), a halftone (30H) image was formed, and the dot reproducibility of this image was evaluated based on the following criteria. The recording medium is high white paper GF-C081 (81.4 g / m 2 A 30H image was used (Canon Marketing Japan Inc.). Note that a 30H image is a halftone image where 256 gradations are expressed in hexadecimal, with 00H being solid white (non-image) and FFH being a solid image (full image). The area of ​​1000 dots in the resulting halftone image was measured using a digital microscope VHX-500 (lens wide range zoom lens VH-Z100 manufactured by Keyence Corporation). The number average (S) of the dot area and the standard deviation (σ) of the dot area were calculated, and the dot reproducibility index was calculated according to the following formula. The dot reproducibility of the halftone image was evaluated using a dot reproducibility index (I). A smaller value of the dot reproducibility index (I) indicates better dot reproducibility. Dot reproducibility index (I) = σ / S × 100 (Evaluation Criteria) A:I is less than 2.0 B: I is 2.0 or more and less than 4.0 C:I is 4.0 or more and less than 6.0 D:I is 6.0 or more and less than 8.0 E:I is 8.0 or higher In this disclosure, ranks A to C are determined to be good dot reproducibility.

[0107] <Environmental Stability Evaluation of Toner Charge Amount> A two-component developer was prepared by putting 9.5 g of magnetic carrier F813-300 (manufactured by Powder Tech Co., Ltd.) and 0.5 g of evaluation toner into a 50c plastic bottle with a lid. This two-component developer was left to stand for 24 hours in a high temperature and high humidity environment (30°C, 85% RH) or a low temperature and low humidity environment (15°C, 10% RH). It was then shaken for 7 minutes at a speed of 150 times / min using a shaker (YS-LD: manufactured by Yayoi Co., Ltd.), and the triboelectric charge amount in the high temperature and high humidity environment and the low temperature and low humidity environment were measured using the device shown in Figure 1. (Method of measuring charge amount) As shown in Figure 1, 0.100 g of the two-component developer for which triboelectric charge is to be measured is placed in a metal measurement container 2 with a 500 mesh (25 μm opening) screen 3 at the bottom, and then the metal lid 4 is placed on the container. The total weight of the measurement container 2 at this time is weighed and taken as Wl (g). Next, the suction machine 1 (the part in contact with the measurement container 2 is at least an insulator) sucks air from the suction port 7, and adjusts the air flow control valve 6 to set the pressure of the vacuum gauge 5 to 250 mmAq. Suction is continued in this state for 2 minutes to remove the toner by suction. The potential of the electrometer 9 at this time is V (volts). Here, 8 is a capacitor with a capacity of C (μF). The weight of the entire measuring container after suction is weighed and is set to W2 (g). The amount of triboelectric charge of this toner is calculated by the following formula. Triboelectric charge (μC / g) = (C × V) / (W1-W2) The evaluation was performed by calculating the ratio of the amount of triboelectric charge at low temperature and low humidity to the amount of triboelectric charge at high temperature and high humidity (amount of triboelectric charge at high temperature and high humidity / amount of triboelectric charge at low temperature and low humidity). In this disclosure, ranks A to C were determined to be good environmental stability. A: Triboelectric charge under high temperature and high humidity / Triboelectric charge under low temperature and low humidity is 0.80 or more B: Triboelectric charge under high temperature and high humidity / triboelectric charge under low temperature and low humidity is 0.65 or more and less than 0.80 C: Triboelectric charge under high temperature and high humidity / triboelectric charge under low temperature and low humidity is 0.50 or more and less than 0.65 D: Triboelectric charge under high temperature and high humidity / Triboelectric charge under low temperature and low humidity is less than 0.50

[0108] [Table 5] [Explanation of symbols]

[0109] 1 suction machine, 2 measuring container, 3 screen, 4 lid, 5 vacuum gauge, 6 air flow control valve, 7 Suction port, 8 capacitor, 9 electrometer

Claims

1. A toner comprising toner particles, the toner particles contain a binder resin, a resin A, a wax and a fatty acid metal salt; The resin A has a substituted or unsubstituted silyl group in the molecule and has a structure represented by the following formula (1): 【Chemistry 1】 (In the formula (1), P 1 represents a polymer moiety, L 1 represents a single bond or a divalent linking group, R 1 to R 3 each independently represent a hydrogen atom, a halogen atom, an alkyl group having 1 or more carbon atoms, an alkoxy group having 1 or more carbon atoms, an aryl group having 6 or more carbon atoms or a hydroxy group, m represents a positive integer, and when m is 2 or more, a plurality of L 1 s, a plurality of R 1 s, a plurality of R 2 s and a plurality of R 3 s may be the same or different.) The substituent of the substituted silyl group is at least one selected from the group consisting of an alkyl group having one or more carbon atoms, an alkoxy group having one or more carbon atoms, a hydroxy group, a halogen atom, and an aryl group having six or more carbon atoms. A toner characterized by:

2. R in the formula (1) 1 ~R 3 The toner according to claim 1 , wherein at least one of the groups represents an alkoxy group or a hydroxy group having one or more carbon atoms.

3. R in the formula (1) 1 ~R 3 The toner according to claim 1 or 2, wherein each independently represents an alkoxy group or a hydroxy group having one or more carbon atoms.

4. P in the formula (1) 1 The toner according to any one of claims 1 to 3, wherein represents a polyester resin moiety or a styrene acrylic resin moiety.

5. The content of the styrene-acrylic resin in the binder resin is 50% by mass or more, and P in the formula (1) 1 The toner according to any one of claims 1 to 4, wherein represents a styrene acrylic resin moiety.

6. The content of the polyester resin in the binder resin is 50% by mass or more, and P in the formula (1) 1 The toner according to any one of claims 1 to 4, wherein represents a polyester resin moiety.

7. 7. The toner according to claim 1, wherein the content of silicon atoms in the resin A is 0.02% by mass to 10.00% by mass.

8. 8. The toner according to claim 1, wherein, when a content of the wax in the toner particles is A% by mass and a content of the fatty acid metal salt in the toner particles is B% by mass, a ratio of B to A (B / A) is 0.0010 or more and 1.0000 or less.

9. 9. The toner according to claim 1, wherein, when a content of the fatty acid metal salt in the toner particles is B mass % and a content of the resin A in the toner particles is C mass %, a ratio of B to C (B / C) is 0.0100 or more and 10.0000 or less.

10. 10. The toner according to claim 1, wherein, when a molar number of silicon atoms derived from the resin A in the toner particles is E and a molar number of metal of the fatty acid metal salt in the toner particles is F, a ratio of E to F (E / F) is 0.100 or more and 10,000 or less.

11. 11. The toner according to claim 1, wherein the wax in the toner particles contains at least one selected from the group consisting of an ester wax and an aliphatic hydrocarbon wax.

12. the wax in the toner particles contains an ester wax, The ester wax is An ester compound of a fatty acid monomer having 8 to 22 carbon atoms and an alcohol monomer, and An ester compound of an aliphatic alcohol monomer having 8 to 22 carbon atoms and an acid monomer. The toner of claim 11, comprising at least one ester compound selected from the group consisting of:

13. 13. The toner according to claim 1, wherein the melting point of the wax in the toner particles is 60.0° C. or more and 100.0° C. or less.

14. 14. The toner according to claim 1, wherein the fatty acid metal salt in the toner particles is a metal salt of a fatty acid and at least one metal selected from the group consisting of Al, Mg, and Zn.

15. 15. The toner according to claim 1, wherein the fatty acid metal salt in the toner particles is a metal salt of a fatty acid having 8 to 22 carbon atoms and a metal.

Citation Information

Patent Citations

  • Electrophotographic toner

    JP1995239573A

  • Developer and image forming device using the developer

    JP1999282194A

  • Toner and its production

    JP2000122341A

  • Electrostatic charge image developing toner

    JP2006259359A

  • Electrophotographic toner, development method, development device, image forming method, and image forming apparatus

    JP2007079304A